(3cJGH JOHjQ GdCeQGV GdMGOIs - (3GHbQGW GdMcjes
(3ChdgG (B:s
(3GdebGdI GdChdi ef cJGH GHbQGW bGd GHbQGW CeG GdCYQGV GdJi JYQV ddeQVi ai cd hGMO ef CeQGVge s
(3BNQgG (B:s
(3hCbd ef jecf GSJYeGdg ajef cGf JOHjQg HGdCTQHI abW JeJ GdebGdI GdKGdKI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs